TAFSIR DEMOKRASI GUS DUR PERSPEKTIF QS. AL-BAQARAH (2): 41 - Achmad Sjamsudin (MIYAH: Jurnal Studi Islam, 2025)
Democracy was first developed in the practice of the city states of Greece and Athens. Then, the growth of the term democracy experienced a fertile period and a shift towards modernization during the renaissance. The history of democratic practice exists in three waves. Indonesia is one of the countries entering wave three. According to Gus Dur, democracy is not an exchange of positions, but rather a principle of state administration where the constitution must be upheld. Gus Dur's democratic principles are interesting from the perspective of QS interpretation. Al-Baqarah (2): 41. This research aims to examine Gus Dur's democratic principles in the perspective of QS interpretation. Al-Baqarah (2): 41. Focuses on articles regarding Democracy, Community Participation, Freedom of Speech and Religion, and Institutional Reform. Also to three books of commentary: al-Zamakhsyari, al-Maraghi, and Abu Hayyan. This research uses the SLR approach, and includes library research. The results of this research are that democracy is a state administration where the constitution must be upheld. The implication is that democracy is not a market or a mere exchange of positions. Gus Dur's democratic principles remain highly relevant and important in Indonesia's current political and social context.